Predictors and moderators of treatment outcome in patients receiving multi-element psychosocial intervention for early psychosis: Results from the GET UP pragmatic cluster randomised controlled trial. (May 2017) - Lasalvia, Antonio; Bonetto, Chiara; Lenzi, Jacopo; Rucci, Paola; Iozzino, Laura; Cellini, Massimo; Comacchio, Carla; Cristofalo, Doriana; D'Agostino, Armando; de Girolamo, Giovanni; De Santi, Katia; Ghigi, Daniela; et al.
Abstract : Background: The GET UP multi-element psychosocial intervention proved to be superior to treatment as usual in improving outcomes in patients with first-episode psychosis (FEP). However, to guide treatment decisions, information on which patients may benefit more from the intervention is warranted. Aims: To identify patients' characteristics associated with (a) a better treatment response regardless of treatment type (non-specific predictors), and (b) a better response to the specific treatment provided (moderators). Method: Some demographic and clinical variables were selected a priori as potential predictors/moderators of outcomes at 9 months. Outcomes were analysed in mixed-effects random regression models. (Trial registration: ClinicalTrials.gov, NCT01436331.) Results: Analyses were performed on 444 patients. Education, duration of untreated psychosis, premorbid adjustment and insight predicted outcomes regardless of treatment. Only age at first contact with the services proved to be a moderator of treatment outcome (patients aged ≥35 years had greater improvement in psychopathology), thus suggesting that the intervention is beneficial to a broad array of patients with FEP. Conclusions: Except for patients aged over 35 years, no specific subgroups benefit more from the multi-element psychosocial intervention, suggesting that this intervention should be recommended to all those with FEP seeking treatment in mental health services.